ANALYZING THE FINANCIAL RATIOS OF PT ASPIRASI HIDUP INDONESIA TBK IN 2024 TO ASSESS FINANCIAL PERFORMANCE - Badmir; Riski Rahmawati; Risti Nazila; Ramziati Piqqa; Asnawi (PT. Radja Intercontinental Publishing, 2024)
This study aims to analyze the financial performance of PT Aspiration Life Indonesia Tbk (formerly PT Ace Hardware Indonesia Tbk ) using the financial ratio analysis method. The research employs a descriptive quantitative approach with secondary data obtained from the company's 2024 financial statements. The analysis focuses on four main financial ratio categories: liquidity, solvency, activity, and profitability. The findings indicate that the company maintains a very strong liquidity position, as reflected by a Current Ratio of 6.81 times and a Quick Ratio of 2.92 times. In terms of solvency, the Debt to Asset Ratio of 20.49% and the Debt to Equity Ratio of 25.78% demonstrate a sound capital structure and low financial risk. The profitability ratios show effective management efficiency, with a Gross Profit Margin of 48.73%, Net Profit Margin of 10.30%, Return on Assets of 10.80%, and Return on Equity of 13.58%. However, the activity ratios indicate a relatively low inventory turnover (1.30 times) and moderate asset utilization efficiency (Total Asset Turnover of 1.05 times). Overall, the company exhibits a stable and promising financial condition, although improvements in inventory management efficiency are necessary to further optimize operational performance.